2022
DOI: 10.1016/j.cmi.2021.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Time to positivity in bloodstream infection is not a prognostic marker for mortality: analysis of a prospective multicentre randomized control trial

Abstract: Time-to-positivity in bloodstream infection is not a prognostic marker for mortality: analysis of a prospective multicentre randomised control trial, Clinical Microbiology and Infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…The results from this study were from a single-region cohort study with a single laboratory, making extrapolations difficult. For example, Hamilton et al [ 17 ] found a median TTP of 17.1 hours in bacteremia with β-hemolytic streptococci compared to the 10.4 hours in our study. The reason for this difference is unknown but could be due to different blood culture systems, different TTP of different groups or species of β-hemolytic streptococci, or logistics.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The results from this study were from a single-region cohort study with a single laboratory, making extrapolations difficult. For example, Hamilton et al [ 17 ] found a median TTP of 17.1 hours in bacteremia with β-hemolytic streptococci compared to the 10.4 hours in our study. The reason for this difference is unknown but could be due to different blood culture systems, different TTP of different groups or species of β-hemolytic streptococci, or logistics.…”
Section: Discussioncontrasting
confidence: 51%
“…Similar findings have been observed with TTP and other Gram-positive bacteria, suggesting that TTP may be an important prognostic factor in patients with bacteremia. However, in a recent study published by Hamilton et al, TTP correlated with mortality rate only for Candida and β-hemolytic streptococci and not for other major pathogens [ 17 ]. In that study, β-hemolytic streptococci were divided into groups based on the Lancefield group antigen, which does not always correlate with the species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Although this is possible, we have previously shown that "time to positivity", a proxy for bacterial load, is no different in transplant patients than non-transplant patients in this cohort, and time to appropriate therapy in this study was the same across both cohorts. 14 Also, in this cohort, infections with Pseudomonas spp (associated with worse outcomes) were higher in the transplant cohort, while coagulase negative staphylococci (often felt to be marginally pathogenic) were higher in the non-transplant cohort. Regardless, given that early therapy improves outcomes in bloodstream infection, even small changes in patient behaviour (e.g.…”
Section: Other Literaturementioning
confidence: 68%
“…A recent meta-analysis concludes that a short TTP is a prognostic marker associated with mortality and septic shock, applicable for most analyzed species except Candida spp., but it has substantial limitations [ 131 ]. Although there is evidence in favor of TTP being associated with worse prognosis in bacteremia due to S. aureus [ 132 , 133 ], E. coli [ 134 ], S. pneumoniae [ 135 ], P. aeruginosa [ 136 ], or K. pneumoniae [ 137 ], not all cases have been able to demonstrate this association between TTP and mortality [ 138 ]. Furthermore, a linear relationship is not always found, with a worse prognosis being described with both short and long TTP for S. aureus [ 139 ], and with long TTP for C. albicans [ 138 , 140 ].…”
Section: Can Time To Positivity Of Blood Cultures Be a Predictor Of E...mentioning
confidence: 99%